Ligação de hidrogênio intermolecular entre CL3CH E F3CH e as espécies receptoras de próton: C2H2, C2H4, C3H4, C3H6 E C4H4 - Pereira, Arquimedes Mariano (2016)
This work deals with the computational quantum study of structural, electronic, vibrational, hyperconjugative and topological of hydrogen complexes with Cl3CH and F3CH donors, with the aceptor species proton, C2H2, C2H4, C3H4, C3H6 and C4H4, interacting with a region high electron density of the type π and pseudo-π. The computational methods used electronic structure were Density Functional Theory with functional hybrids B3LYP and X3LYP with Perturbative and Theory of many bodies of order 2, with a series of bases. The amounts of hydrogen bond energy suffered superposition error corrections of the Basic Feature Set and Vibrational Zero Point Energy. The complexes of hydrogen with the donor Cl3CH showed increases in the length of the C-H bond, while the present F3CH shortening of the C-H bond length due to formation of intermolecular bond. This trend is found for the deviation in the infrared spectrum, Chloroform has red shift while Fluoroform has blue shift deviations. The use of quantum theory of atoms in molecules shows the change in electron density of both interacting species, and in addition the density values are small and the Laplacian are positive. The methods followed the same trend for the properties of interest, suggesting the use of calculations via density functional theory, due to lower computational demand to study such systems.